Effect of slip condition on viscoelastic MHD oscillatory forced convection flow in a vertical channel with heat radiation - Singh, K.D. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper an oscillatory flow of a viscoelastic, incompressible and electrically conducting fluid through a porous medium bounded by two infinite vertical parallel plates is discussed. One of these plates is subjected to a slip-flow condition and the other to a no-slip condition. The pressure gradient in the channel oscillates with time. A magnetic field of uniform strength is applied in the direction perpendicular to the plates.
Keywords: oscillatory; MHD; forced convection; viscoelastic; slip-flow; porous medium